Strengthening the Role of Cyber Security for Students in Addressing Information Security Threats in the Era of Artificial Intelligence - Taufik Iqbal Ramdhani; Dwi Utari Iswavigra; Deny Prasetyo; Yulaikha Mar'atullatifah; Ardy Wicaksono; Suyahman Suyahman (Jurnal Pengabdian IPTEK, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed the digital ecosystem, particularly in the fields of education and information systems. While AI provides various benefits in supporting learning processes and digital services, it also introduces new challenges related to information security. The increasing use of AI-driven technologies has expanded the risk of cyber threats, including data breaches, phishing, malware attacks, and unauthorized access to personal and academic information. Students, as active users of digital platforms and AI-based applications, are among the most vulnerable groups facing these emerging risks. This community service activity aims to strengthen the role of cyber security for students in addressing information security threats in the era of Artificial Intelligence. The activity was conducted using a hybrid seminar model involving 48 students from Universitas Sugeng Hartono. The on-site session took place in Room 15 of Universitas Sugeng Hartono, Solo Baru, Sukoharjo, Central Java, while the speaker delivered the material online through Zoom on Thursday, January 29, 2026. The seminar focused on introducing fundamental concepts of Artificial Intelligence, emerging cyber threats, and the importance of cyber security awareness in digital environments. The results of the activity indicate a positive impact on students’ understanding and awareness of information security issues. Participants demonstrated high levels of enthusiasm, actively engaged in discussions, and raised critical questions related to the safe use of AI technologies and cyber security practices. Overall, this activity contributed to enhancing students’ digital literacy and emphasized the importance of cyber security as a key component in mitigating information security risks in the era of Artificial Intelligence.